The Ingenious Synthesis of a Nitro-Free Insensitive High-Energy Material Featuring Face-to-Face and Edge-to-Face π-Interactions - Zhai, Lianjie; Bi, Fuqiang; Huo, Huan; Luo, Yifen; Li, Xiangzhi; Chen, Sanping; Wang, Bozhou (Frontiers in Chemistry, 2019)
Density, detonation property, and sensitivity may be the most valued features when evaluating an energetic material. By reasoning structure–property relationships, a nitro-free planar energetic material with high nitrogen and oxygen content, 7-hydroxy-difurazano[3,4-b:3’,4’-f]furoxano[3’’,4’’-d]azepine (4), was synthesized using a unique and facile approach. The structure was fully characterized by IR and NMR spectra, elemental analysis, differential scanning calorimetry (DSC), and single-crystal X-ray diffraction. The expected properties of 4, including a high density of 1.92 g cm−3, high detonation velocity of 8875 m s−1, and low mechanical sensitivities (impact sensitivity, 21 J and friction sensitivity, >360 N), confirm our strategy. Interestingly, the single-crystal structures of 4 reveal expected face-to-face and unprecedented edge-to-face π-interactions in the crystal stacking. The remarkable differences in crystal stacking of 4 provide unequivocal evidence that face-to-face π-π interactions contribute significantly to closer assembly and higher density.